Capacity Building for Tuha Peut in the Implementation of the Qanun Concerning the Prevention of Chronic Energy Deficiency Pregnant Women in Gampong Blang Sapek - Vira Novita Sari; Siti Maisyaroh Fitri Siregar; Teungku Nih Farisni; Fitriani Fitriani (Universitas Islam Negeri Sumatera Utara, Medan, 2023)
Medium Term Development Plan 2020-2024 responsible to improve health servicesso that everyone in the country has access to basic health services. They will drive increased prevention efforts, and use technology to help do so.The percentage of pregnant women at risk of Chronic Energy Deficiency can be marked by the size of the Upper Arm Circumference of less than 23.5 cm. The purpose is to find out how Tuha Peut's capacity building is in implementing the Qanun on the prevention of Chronic Energy Deficiency in pregnant women in Gampong Blang Sapek. Using qualitative research with a descriptive approach. Observations show that some Tuha Peut still do not know the importance of preventing Chronic Energy Deficiency in accordance with Gampong Blang Sapek Qanun No 03 of 2022 because in terms of knowledge they are still lacking and the capacity of Tuha Peut Gampong Blang Sapek is still low, this is evidenced from the results of the FGD activities where Some Tuha Peuts still don't understand the Gampong Blang Sapek Qanun No. 03 concerning guidelines for the prevention and management of SEZs in pregnant women. Based on the input and process components, it shows that funds for Chronic Energy Deficiency prevention activities are still insufficient and all prevention mechanisms have not been implemented. The output component shows the activities of preventing and handling SEZs for pregnant women carried out by the village government of Blang Sapek together with tuha peut, cadres and health workers, namely mapping the status of pregnant women with the Stunting rembug program, active integrated service post, Establishment or Strengthening of the Village Nutrition House and classes for pregnant women.Keywords: Capacity Building, Tuha Peut, Qanun